INFORMATION SYSTEM PROCUREMENT OF GOODS IN. SUBA INDAH TBK USING VISUAL BASIC 6.0 - Agus Sobari (Jurnal Sistem Informasi, 2008)
Making Procurement System program is needed to help the user especially in thesearch process or the data items needed by the user, and the mistakes that happenedthe very small because the process is computerized.Based on the results of the discussion on this issue, it can be concluded:1.Sistem computerization is very useful for easy, smooth flow of information data aswell as reduce the risk of counting errors in recording and storage of goods in thetransaction process from the supplier.2. Finding and recording of data faster and more accurate3. With fast service could not be separated from efforts to improve the existingsystem to run optimally and can provide a positive contribution to the company.4. Making the report can be presented much more quickly and accurately inaccordance with what is in want of an appeal with the manually.